A rational approach to beam path planning in additive manufacturing: the inverse heat placement problem. (22nd February 2023) - Yang, Yue; Billingham, John; Axinte, Dragos; Liao, Zhirong
Abstract : High demand for components with complex geometries at macro and micro levels drives the development of additive manufacturing (AM). However, the scientific basis for designing energy beam scanning strategies (e.g. beam scanning speed, beam path, beam power) still relies on trial and error approaches (i.e. experimental/simulation of predefined beam trajectories) followed by the evaluation of process outcomes (e.g. structural/metallurgical properties of the built parts); this is the Direct Problem. To address such drawbacks, this paper reports, for the first time, a mathematical model for selecting key parameters related to beam exposure time in AM processes as an attempt to improve the build part's uniform properties, i.e. the Inverse Heat Placement Problem. Our algorithm yields variable beam scanning speeds and optimized beam paths for achieving a desired maximum temperature distribution (uniform or target pattern) and is suitable for different circumstances and scanning strategies dependent on the print part configuration. Here, raster and spiral predefined beam paths are chosen as examples. Variable beam scanning speeds and optimized beam paths obtained from our algorithm are able to induce a desirable uniform maximum temperature distribution compared with the conventional approach of constant beam scanning speeds and a predefined beam path.